Why trauma must trump burn injuries: The spectre of missed injuries - Marc R. Matthews; Lauren M. Van Sant; Stephanie E. Bollenbach; Scott D. Swanson; Alexzandra K. Hollingworth; Kevin N. Foster (Elsevier, 2019)
Significant burn injury in the setting of trauma poses a challenging clinical dilemma and can be a diversion to providers not familiar with such injuries. Approximately 5-7% of burn center admissions include patients with multiple traumatic injuries. A 44 year old male with poly-trauma due to a factory explosion presented with significant burns, and a pneumothorax, compartment syndromes of bilateral hands and forearms, and a missed axillary vein injury. In burn-trauma patient evaluations, thorough primary, secondary, and especially the tertiary surveys of the Advanced Trauma Life Support (ATLS®) and Advanced Burn Life Support (ABLS®) protocols must be performed and frequently reevaluated to avoid missed trauma injuries in the presence of thermal injury. This is especially important in blasts, explosions, assaults, and terror attacks at anytime and anywhere, when combined burn and trauma injuries are common. Early resuscitation of these patients mandates that frequent assessments uncover all other traumatic injuries, which may be less dramatic but more lethal than the burn. Keywords: Trauma, Burn, Missed injuries, ATLS, Axilla, Compartment syndrome